Wireless Ear-EEG Sensor - Ab Razak, Abdul Rauf (Universiti Sains Malaysia, 2018)
The brain monitoring based on the electroencephalography (EEG) into everyday life has been prolonged by the limited portability and long setup time of current wearable systems as well as by the invasiveness of implanted systems. A method for recording the EEG signal from the outer ear called ear-EEG, has been proposed which leading to the discreet, unobtrusive, and user-friendly approach to the brain monitoring. The ear-EEG recording concept is tested using several standard EEG paradigms, benchmarked against standard on-scalp EEG, and its feasibility proven. This system offers number of advantages including fixed electrode position, user comfort, robustness to electromagnetic interference, feedback to the user, and ease to use. This project also supposed to design a wireless EEG acquisition system for easily monitoring of the patients. In the other word, the purpose of this study is to design a wireless ear-EEG sensor for better monitoring. The development of wireless EEG system is also suitable for the application such as remote control of devices, rescue, and so on.